A Longitudinal Study of the Relationships between Haemostatic, Lipid, and Oestradiol Changes during Normal Human Pregnancy - Sattar, Naveed; Greer, Ian A.; Rumley, Ann; Stewart, Grace; Shepherd, James; Packard, Chris J.; Lowe, Gordon D. O. (Thrombosis and Haemostasis, 1999)
Increased activation of both blood coagulation and fibrinolysis occurs during normal pregnancy. The responsible mechanisms are unclear, but may include increases in both oestradiol and blood lipids. We, therefore, studied the associations between fasting serum oestradiol, plasma cholesterol and triglyceride, and Factor VII activity, PAI activity, t-PA antigen, fibrin D-dimer, and vWF antigen in 10 women, each sampled on 6 occasions between 10 weeks and 35 weeks during normal pregnancy. Strong and similar individual correlations were observed between increases in FVII, PAI, t-PA and D-dimer (but not vWF) and increases in both oestradiol and triglyceride. Associations between increments in plasma cholesterol and haemostatic factors (except for FVII), were somewhat weaker. We, therefore, suggest that oestradiol-induced hypertriglyceridaemia may be a cause of elevations in plasma Factor VII activity, PAI and t-PA, and fibrin turnover (D-dimer) during normal pregnancy, but is poorly related to the increase in vWF antigen.